2005
DOI: 10.1002/cncr.21088
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of SOX Group B (SOX1, 2, 3) and ZIC2 antibodies in Turkish patients with small cell lung carcinoma and their correlation with clinical parameters

Abstract: BACKGROUNDExpression of neuroectodermal markers is a key feature of small cell lung carcinoma (SCLC). Although immune responses against a number of these proteins have been associated with paraneoplastic neuronal disease (PND), most patients with SCLC have anti‐neuroectodermal antibodies in the absence of PND. Whether these immune responses affect the clinical outcome in SCLC is critical in understanding the potential value of these proteins as cancer vaccine targets as well as in the pathogenesis of PND.METHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
61
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 44 publications
6
61
0
3
Order By: Relevance
“…Our results confirmed the utility of this approach to identify tumor-associated antigens including HuC recognized by autoantibodies in sera from patients with lung cancer (12,13).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our results confirmed the utility of this approach to identify tumor-associated antigens including HuC recognized by autoantibodies in sera from patients with lung cancer (12,13).…”
Section: Discussionsupporting
confidence: 81%
“…Hanash (11) has described that harnessing the immune response to identify novel cancer biomarkers is an attractive strategy, because the immune system performs biological amplification which is equivalent to a PCR reaction by generating a detectable signal, with antigenic tumor proteins as templates, beginning at an early stage during tumor development when the tumor may be otherwise undetectable. Many tumor-related autoantibodies have been reported in pulmonary carcinomas (12)(13)(14)(15). Thus, an exhaustive search for novel tumor-specific autoantibodies, which may serve as early sero-diagnostic markers for cancers, has commenced.…”
Section: Introductionmentioning
confidence: 99%
“…Initially identified by serological analysis of expression cDNA libraries (SEREX; ref. 7), the presence of SOX2 autoantibodies (SOX2-Abs) in SCLC patients has been confirmed by several subsequent studies (6)(7)(8)(9)(10). The 22% to 33% frequency of SOX2-Abs has promising potential for clinical use.…”
Section: Introductionmentioning
confidence: 80%
“…To date, the immunogenicity of SOX2 had mainly been investigated in individuals with small cell lung carcinoma (SCLC; refs. [6][7][8][9][10]. Initially identified by serological analysis of expression cDNA libraries (SEREX; ref.…”
Section: Introductionmentioning
confidence: 99%
“…Hanash (Hanash, 2003) reported that analyzing the immune response to identify novel cancer biomarkers is an attractive strategy, because the immune system induces biological amplification that is equivalent to a polymerase chain reaction (PCR) by generating a detectable signal with antigenic tumor proteins as templates, beginning at a very early stage during tumor development before the tumor identifiable. Some tumor-associated autoantibodies have also been reported for lung cancer (Vural et al, 2005;Yagihashi et al, 2005).…”
Section: Introductionmentioning
confidence: 95%